Information Technology Governance Design in Trading Companies Using the COBIT 2019 Framework - Leonardo, Kevin; Latuperissa, Rudi (Universitas Bina Darma, 2024)
Effective information technology (IT) governance is very important for trading companies in managing their information assets well. The COBIT 2019 has been recognized as an international standard for IT governance that helps organizations achieve their strategic goals through the implementation of structured practices and processes. This research aims to design an IT governance framework based on COBIT 2019, especially for trading companies. The research methodology uses a case study approach by analyzing the unique needs and characteristics of trading companies in the IT context. The result is a design that is tailored to the needs and challenges faced by trading companies, including aspects of information security which are crucial in today's digital era. This research contributes to IT practitioners and senior managers to understand the practical and effective implementation of COBIT 2019 in improving IT governance in trading companies. By using COBIT 2019, trading companies can optimize the management of their information assets while ensuring regulatory compliance and increasing stakeholder trust.